Salt: Should I Cut Back? - Asmaa Fatani; Nancy J. Gal; Wendy Dahl (EDIS, 2018)
Dietary salt is made up of sodium and chloride, two essential minerals necessary for good health. Sodium is very important for our body to maintain fluid balance, blood volume, and blood pressure. However, many people consume more dietary sodium (from salt) than needed. Decreasing dietary sodium has received a lot of attention in recent years due to its association with high blood pressure (hypertension) and cardiovascular disease (Kloss, Meyer, Graeve, & Vetter, 2015). This publication explore ways to decrease sodium intake and the health effects of inadequate and excessive sodium intakes.